2003
DOI: 10.1080/0955300031000140775
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafractionation in A7 human malignant glioma in nude mice

Abstract: Despite a pronounced HRS phenomenon in vitro, UF was significantly less effective than CF in A7 human malignant glioma in nude mice. These results neither disprove the existence of HRS nor do they exclude a possible clinical value of UF. The findings rather indicate that simplistic extrapolation from results obtained after single-dose exposure or few fractions in vitro is not sufficient to predict outcome of UF in vivo and that comprehensive evaluation of novel treatment options in animal models continues to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
1
29
2
Order By: Relevance
“…31 It was found that the low-dose ultra-fractionation caused a significant decrease in tumor growth delay but increased the top-up TCD 50 dose and further failed to prove the existence of HRS in in-vivo. 32 It was not clear from the results of this report that there existed any potential utility of low-dose ultra-fractionation in translating to clinical practice. 31 However, in another recent report, repeated irradiation with low dose (0.8 Gy 3 times / day for 4 days/week to a total of 2 consecutive weeks) was markedly more effective than irradiation with single conventional dose (2 Gy / day, for 4 days/week to a total of 2 consecutive weeks) in inhibiting the tumor xenograft in mice.…”
Section: Discussioncontrasting
confidence: 44%
“…31 It was found that the low-dose ultra-fractionation caused a significant decrease in tumor growth delay but increased the top-up TCD 50 dose and further failed to prove the existence of HRS in in-vivo. 32 It was not clear from the results of this report that there existed any potential utility of low-dose ultra-fractionation in translating to clinical practice. 31 However, in another recent report, repeated irradiation with low dose (0.8 Gy 3 times / day for 4 days/week to a total of 2 consecutive weeks) was markedly more effective than irradiation with single conventional dose (2 Gy / day, for 4 days/week to a total of 2 consecutive weeks) in inhibiting the tumor xenograft in mice.…”
Section: Discussioncontrasting
confidence: 44%
“…5 Despite this HRS in vitro, the efficacy of ultrafractionation (126 fractions of 0.4 Gy over 6 weeks) in A7 tumor xenografts in nude mice was significantly less than the effect of conventional treatment (30 fractions of 1.68 Gy over 6 weeks) using both tumor growth delay and top-up TCD 50 as experimental end points. 6 It is our view that the data of Beauchesne et al 1 do not demonstrate an improvement in the effectiveness of radiotherapy in human malignant gliomas by ultrafractionation and do not provide a preclinical rationale for or against clinical trials. In contrast, the data on A7 glioma clearly show a need for further preclinical investigations with appropriate end points to explore whether clinical trials on ultrafractionation are indicated.…”
Section: Dear Sirmentioning
confidence: 96%
“…Krause et al tested the ultrafractionated regimen in an animal model grafted with cells derived from the A7 human cell line which expressed the HRS phenomenon (Krause et al, 2003). Cryoprereserved tumor tissue was transplanted subcutaneously onto the backs of five mice.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…The tumor with the median volume doubling time was transplanted onto the back of another eight to 12 mice. 1-2 mm pieces of tissue from the median tumor were then transplanted subcutaneously into the right hind leg of the experimental animals (Krause et al, 2003). Irradiation protocols were started daily when the tumours reached a mean diameter of 5 mm, corresponding to a volume of 57 mm 3 ; the ultrafractionated regimen consisted of 26 fractions over 6 weeks (0.4 Gy per fraction, 3 fractions per day, 21 fractions per week, spaced at 6 hour intervals), and conventional treatment consisted of 30 fractions over 6 weeks (1.68 Gy per fraction, once daily, 5 fractions per week) (Krause et al, 2003).…”
Section: In Vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation